Dashboard IoT Remote Lab with MQTT Protocol - Hayashi, Victor Takashi; de Almeida, Felipe Valencia; Harada, Lucas Yuji; Hayashi, Fabio Hirotsugu; Arakaki, Reginaldo (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2021: Anais Estendidos do XXVII Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2021.17614, 2021)
The Internet of Things enables the data collection of the physical world in real time, raising opportunities for cost reduction and optimization at large scale. However, creating an IoT solution that transforms these data into information by enabling new visualizations and interactions is not trivial. A remote digital electronics lab tool based on the MQTT protocol with energy monitoring, device control and integration with web and mobile dashboards is presented to support remote learning. The open source tool might be useful for teachers and technical staff of digital electronics lab courses by automating the remote lab devices management.